2017
DOI: 10.15252/emmm.201606602
|View full text |Cite|
|
Sign up to set email alerts
|

The transcription factor GATA 4 promotes myocardial regeneration in neonatal mice

Abstract: Heart failure is often the consequence of insufficient cardiac regeneration. Neonatal mice retain a certain capability of myocardial regeneration until postnatal day (P)7, although the underlying transcriptional mechanisms remain largely unknown. We demonstrate here that cardiac abundance of the transcription factor GATA4 was high at P1, but became strongly reduced at P7 in parallel with loss of regenerative capacity. Reconstitution of cardiac GATA4 levels by adenoviral gene transfer markedly improved cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 49 publications
0
60
0
1
Order By: Relevance
“…In mice, cardiomyocyte GATA4 promotes intrauterine cardiac development, in part by driving cardiomyocyte proliferation; however, in the adult, GATA4 triggers cardiac hypertrophy, cell survival, and angiogenesis during pressure overload (17)(18)(19). As demonstrated by us and others, the high cardiac levels of GATA4 shortly after birth are necessary for neonatal mouse heart regeneration after myocardial injury at P1, as well as for zebrafish cardiac regeneration, because GATA4 promotes cardiomyocyte proliferation and capillary growth (15,20,21).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In mice, cardiomyocyte GATA4 promotes intrauterine cardiac development, in part by driving cardiomyocyte proliferation; however, in the adult, GATA4 triggers cardiac hypertrophy, cell survival, and angiogenesis during pressure overload (17)(18)(19). As demonstrated by us and others, the high cardiac levels of GATA4 shortly after birth are necessary for neonatal mouse heart regeneration after myocardial injury at P1, as well as for zebrafish cardiac regeneration, because GATA4 promotes cardiomyocyte proliferation and capillary growth (15,20,21).…”
Section: Introductionmentioning
confidence: 82%
“…In order to be able to induce regeneration in patients suffering from pressure overload-induced cardiomyopathy in the future, one needs to identify crucial upstream regulators that promote this regenerative response. We have previously shown that GATA4 is highly abundant in the myocardium of 1-day-old mice and that it is essential for cardiac regeneration after myocardial infarction at this age, but its expression is dramatically reduced by P7 (15). Crossing our RNA-seq results from the current study with published myocardial GATA4 ChIP-seq data revealed that the majority (74%) of the upregulated genes in the regenerative compared with the nonregenerative phase after nTAC are bound by GATA4 in proximity to their TSS and are therefore likely direct targets of GATA4 (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations